HUBUNGAN DAYA LEDAK OTOT LENGAN BAHU DENGAN KECEPATAN PUKULAN GYAKU TSUKI ATLET KARATE CADET PUTRI DOJO KULIM PEKANBARU - Vera Mita Swastika; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the gyaku tsuki hit still lacking, this is seen when the athlete does kumite and several factors are causing inaccurate hit to the target. The type of this research is a type of correlation research that is used to compare a measurement of two different variables in order to determine the level of the correlation between the variables. The population in this research is karate athlete female cadet Dojo Kulim Pekanbaru amount to 12 people. The sampling technique is by using total sampling, where the total population is sampled. The purpose of this research is to look at the correlation of the shoulder arm muscle explosive power with the gyakutsuki hit speed of karate athlete female cadet Dojo Kulim Pekanbaru. The instrument in this research is using two hand medicine ball put to measure the explosive power of the shoulder arm muscle and the hit speed test is to measure the speed of the gyaku tsuki hit. Test data is using the normality test, moment correlation product test, significant test α = 0.05. Normality test variable X, L0max (0.1658) <Label (0.242), and variable normality test Y, L0max (0.1808) <Ltabel (0.242) in other words the confidence level of 95% normal data and research conclusion indicates: where there is a significant correlation between the correlation of arm and shoulder muscle explosive power with gyaku tsuki hit speed, with a correlation r = 0.6428 where r count> r table or 0.6428> 0.576. And relationship is categorized as strong. Thus, Ha is accepted.Keywords: Correlation, Arm and Shoulder Muscle Explosive Power, The Hit Speed